Market Share Industri Keuangan Non Bank (IKNB) Syariah Di Indonesia: Analisis Pengaruh Profitabilitas Dan Efisiensi - Yayat Supriyatna; Heraeni Tanuatmodjo; Muhamad Arief Ramdhany; Imas Purnamasari (Jurnal Pendidikan Akuntansi & Keuangan, 2023)
This research aims to examine the picture and analyze the effect of profitability and efficiency on the market share of the Islamic Non-Bank Financial Industry (IKNB). The market share growth of the IKNB over the last three years has tended to increase. However, this increase is still below the expected target of 5%. The research method used in this research is descriptive and quantitative methods. The population in this research is the Islamic Non-Bank Financial Industry (IKNB) company. The method used for sampling in this study is purposive sampling with predetermined criteria. With a total sample of 6 Islamic Non-Bank Financial Industry (IKNB) companies. for 3 years with a total of 216 observation data. The data used is secondary data. Statistical analysis technique used in this research is panel data regression analysis with Eviews software version 9. The dependent variable in this study is market share and the independent variables in this study are profitability and efficiency. The results show that profitability and efficiency together affect the market share with a contribution of 26% and the remaining 74% is influenced by other factors not examined in this study. Partially, profitability has a negative and significant effect on market share. The implication of this research is that companies need to increase their profits by managing the assets produced to generate profits. Increased profits will affect the company's good performance so that it has implications for the company's market share.